2012
DOI: 10.1371/journal.pone.0053382
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Podoplanin Expression in Encapsulating Peritoneal Sclerosis

Abstract: Encapsulating peritoneal sclerosis (EPS) is a life threatening complication of peritoneal dialysis (PD). Podoplanin is a glycoprotein expressed by mesothelial cells, lymphatic endothelial cells, and myofibroblasts in peritoneal biopsies from patients with EPS. To evaluate podoplanin as a marker of EPS we measured podoplanin mRNA and described the morphological patterns of podoplanin-positive cells in EPS. Included were 20 peritoneal biopsies from patients with the diagnosis of EPS (n = 5), patients on PD witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Braun et al first reported that the presence podoplaninpositive fibroblast-like cells was a good marker of EPS [11,12]. Podoplanin was first described as a molecule expressed on glomerular podocytes [27] and was later was found to be a useful marker of lymphatic endothelial [28] and mesothelial cells [29].…”
Section: Significance Of Podoplanin Expression In New Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Braun et al first reported that the presence podoplaninpositive fibroblast-like cells was a good marker of EPS [11,12]. Podoplanin was first described as a molecule expressed on glomerular podocytes [27] and was later was found to be a useful marker of lymphatic endothelial [28] and mesothelial cells [29].…”
Section: Significance Of Podoplanin Expression In New Membranesmentioning
confidence: 99%
“…Macroscopic findings of abdominal organs suggested a newly formed encapsulating membrane, mainly in the visceral peritoneum, was unique to EPS [10]. Histologically, the structure of encapsulating membrane was described as organized fibrosing tissue formed on the peritoneal membrane proper with swollen fibroblast-like cells immunohistochemically positive for podoplanin [11,12]. These observations suggested that a definite pathological diagnosis of EPS requires macroscopic and/or histological confirmation of an encapsulating membrane.…”
Section: Introductionmentioning
confidence: 95%
“…We have previously described a population of podoplanin-positive cells in peritoneal biopsies from patients with EPS [3,4]. These cells coexpress smooth-muscle actin (SMA; a marker of myofibroblasts) and podoplanin.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that 15 of 18 biopsies from patients with EPS demonstrated a diffuse accumulation of podoplanin-positive cells [3], whereas these cells were focally present in 3 of 16 specimens from PD patients without signs of EPS, and in none of the 35 controls [3]. Podoplanin-positive cells appear in four morphological patterns [4]. An organized pattern was found in 8 of 24 biopsies, with longitudinal layers of podoplanin-positive cells, a diffuse pattern (in 7 of 24 biopsies) with a random and at times dense podoplanin-positive cell accumulation, and a combination of those two patterns (‘mixed' in 5 of 24 biopsies) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation